The epidemiology and characteristics of injuries to under 5's in a secondary city in Uganda: a retrospective review of hospital data. Issue 4 (2nd October 2022) - Puvanachandra, P.; Ssesumugabo, C.; Balugaba, B. E.; Ivers, R.; Kobusingye, O.; Peden, M.
Abstract: Child injuries are largely preventable yet cause significant mortality and morbidity globally. Injury data from low-income countries is limited for children under the age of 5 and therefore the current understanding of the magnitude of injuries in this age group is low. Hospital-based registries are one mechanism by which injury data can be gathered. This paper presents findings from a retrospective hospital record review of 4 hospitals in Jinja, a rural setting in Uganda, involving the extraction of data for children under the age of 5-years who sustained an injury during a 6-month period in 2019. A total of 225 injury cases were retrieved from the hospitals. Over half (57.3%) of the events occurred among males. The majority (92%) suffered one injury per injury event. Most of the injuries occurred among those aged 13 to 24 months (32.9%). Burns (32%) and cuts (20%) were the most common cause of injury. This study presents a hospital-based analysis of injuries amongst under 5's in rural Uganda. It provides information on the characteristics of children entering healthcare facilities in Uganda and highlights the burden of paediatric injuries in the hospital setting.